2010
DOI: 10.1152/ajpheart.00527.2009
|View full text |Cite
|
Sign up to set email alerts
|

Na+-K+-ATPase and Ca2+clearance proteins in smooth muscle: a functional unit

Abstract: The Na(+)-K(+)-ATPase (NKA) can affect intracellular Ca(2+) concentration regulation via coupling to the Na(+)-Ca(2+) exchanger and may be important in myogenic tone. We previously reported that in mice carrying a transgene for the NKA alpha(2)-isoform in smooth muscle (alpha(2sm+)), the alpha(2)-isoform protein as well as the alpha(1)-isoform (not contained in the transgene) increased to similar degrees (2-7-fold). Aortas from alpha(2sm+) mice relaxed faster from a KCl-induced contraction, hypothesized to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
4
25
0
1
Order By: Relevance
“…These Na ϩ and Ca 2ϩ transporter protein distribution patterns are very similar to those in rodent arterial myocytes and some other cell types (26,31,39,46,48,54). The implication of this structural organization, consisting of units (plasmerosomes) of PM microdomains closely opposed to junctional SR, is that the ␣ 2 -Na ϩ pumps, NCX1 and ROCs (of which TRPC6 proteins are components), and the SR are also functionally linked (8).…”
Section: A B C D Esupporting
confidence: 58%
“…These Na ϩ and Ca 2ϩ transporter protein distribution patterns are very similar to those in rodent arterial myocytes and some other cell types (26,31,39,46,48,54). The implication of this structural organization, consisting of units (plasmerosomes) of PM microdomains closely opposed to junctional SR, is that the ␣ 2 -Na ϩ pumps, NCX1 and ROCs (of which TRPC6 proteins are components), and the SR are also functionally linked (8).…”
Section: A B C D Esupporting
confidence: 58%
“…␣ 1 -Na ϩ pump, NCX1, SERCA2, and PMCA proteins were all upregulated in both the aorta and gastric antrum. Contraction-related proteins (actin and 20-kDa myosin light chain) were, however, unaffected (42,43).…”
Section: Ca 2ϩ Transporter Expression Correlates With ␣ 2 -Na ϩ Pump mentioning
confidence: 94%
“…Prior immunoblot studies (42,43) of the aorta and gastric antrum in ␣ 2 SM-Tg mice revealed that not only the ␣ 2 -Na ϩ pumps but also other Na ϩ and Ca 2ϩ transporters were affected in these SM-containing tissues. ␣ 1 -Na ϩ pump, NCX1, SERCA2, and PMCA proteins were all upregulated in both the aorta and gastric antrum.…”
Section: Ca 2ϩ Transporter Expression Correlates With ␣ 2 -Na ϩ Pump mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to cardiac muscle, it has been demonstrated that the PMCA accounts for the bulk of Ca 2ϩ extrusion from vascular smooth muscle, and its inhibition prolongs aortic relaxation to a similar extent to that of SERCA while NCX inhibition has little effect (298), and in myometrial resistance arteries PMCA inhibition mimics the phenotype of preeclamptic vessels (398). As described in section IIIA, PMCA1 has been identified in numerous studies as a leading candidate gene for the development of hypertension.…”
Section: Pmca and The Vasculaturementioning
confidence: 99%